2016
DOI: 10.1027/1015-5759/a000263
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Problem-Solving Assessed Via Microworlds

Abstract: Abstract. In this study, we explored the network of relations between fluid reasoning, working memory, and the two dimensions of complex problem solving, rule knowledge and rule application. In doing so, we replicated the recent study by Bühner, Kröner, and Ziegler (2008) and the structural relations investigated therein [ Bühner, Kröner, & Ziegler, (2008) . Working memory, visual-spatial intelligence and their relationship to problem-solving. Intelligence, 36, 672–680]. However, in the present study, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 19 publications
7
23
0
Order By: Relevance
“…These results complement the mixed pattern of previous findings, in which working memory explained CPS variance above and beyond intelligence (Wittmann and Süß, 1999), was the only predictor of CPS variance when simultaneously considering figural reasoning (Bühner et al, 2008), but did not explain CPS variance above and beyond reasoning (Greiff et al, 2016). In our view, there is little unique criterion variance to explain because the predictors are highly correlated.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results complement the mixed pattern of previous findings, in which working memory explained CPS variance above and beyond intelligence (Wittmann and Süß, 1999), was the only predictor of CPS variance when simultaneously considering figural reasoning (Bühner et al, 2008), but did not explain CPS variance above and beyond reasoning (Greiff et al, 2016). In our view, there is little unique criterion variance to explain because the predictors are highly correlated.…”
Section: Discussionsupporting
confidence: 89%
“…Working memory is considered the most important cognitive resource for complex information processing, which includes reasoning (e.g., Kyllonen and Christal, 1990; Süß et al, 2002; Conway et al, 2003), language comprehension (e.g., King and Just, 1991), and math performance (e.g., Swanson and Kim, 2007). Consequently, previous research has found a significant relation between WMC and CPS (e.g., Wittmann and Süß, 1999; Bühner et al, 2008; Schweizer et al, 2013; Greiff et al, 2016). However, whether the more basic construct (i.e., WMC) is a stronger symmetrical predictor of CPS than reasoning from the perspective of the Brunswik symmetry principle (Wittmann, 1988) is not clear (for an overview, see Zech et al, 2017).…”
Section: Part I: Empirical Investigation Of the Cognitive Prerequisitmentioning
confidence: 94%
“…For answering this question, we utilized the data from the study of Bühner, Krumm, Ziegler, and Plücken [5] and compared the results to those of Wittmann and Süss [1], Bühner, Kröner, and Ziegler [6], and Greiff, Krkovic, and Hautamäki [7]. Note, however, that the present analyses of the Bühner et al [5] data are novel, as the previous publication based on these data did not include the results of the problem solving scenario, due to a different research focus.…”
Section: Introductionmentioning
confidence: 99%
“…As a response to this need, complex problem solving (CPS) has received considerable attention over the last couple of years as one potential extension of current theories. Both its role within the nexus of other cognitive abilities as well as its assessment are currently under intensive scientific investigation [8,9,10,11]. The core of this special issue is to shed further light on the role of CPS within the broad field of research on the human intellect.…”
mentioning
confidence: 99%